4x+36=-2

Simple and best practice solution for 4x+36=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+36=-2 equation:


Simplifying
4x + 36 = -2

Reorder the terms:
36 + 4x = -2

Solving
36 + 4x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + 4x = -2 + -36

Combine like terms: 36 + -36 = 0
0 + 4x = -2 + -36
4x = -2 + -36

Combine like terms: -2 + -36 = -38
4x = -38

Divide each side by '4'.
x = -9.5

Simplifying
x = -9.5

See similar equations:

| 5/7=10/(x+2) | | 9a-3(a-6)=-6 | | 5x-9+2=-2x+6 | | 2/x-3+5/x+2 | | 4x^2+9y^2-16x-18y+24=0 | | 32/1 | | (2x/3)-1=(x-2)/2 | | .22y-.6=.12y+1-.7y | | 5m-18=-4+3m | | 5(x+2)=x-6 | | x-.7=8.18 | | 13s=78 | | 6y-3x=-8 | | 9(3q-4)= | | 1/(4y-15) | | 2x+3x=63x | | (4/5)^3 | | 12x+5=36-51x | | (1/3)^5 | | (18x-6)+(8x+4)=180 | | 6x-2*(4x-1)=7 | | 4n+5n= | | 16x-32=16x+18 | | N=.733(43)+8.398 | | 2/20=7/n | | 3+9r-1=7r+12-3r | | 10/8=t/12 | | 3x-3.6=7x-8.6 | | 2x^4+3x^3+6x^2+12x-8=0 | | 5s+6s=88 | | x^4-4*x^3+5*x^2-4*x+1=0 | | 117=.75x+27 |

Equations solver categories